Mid-term Results of Hybrid Myocardial Revascolarization for the Patients with the Coronary Arteries Disease - Gabrielyan, A.; Domansky, T.; BeregovoyО. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Introduction. Myocardial revascularization using traditional percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) is indicated to the patients with multivessel coronary artery (CA) damage. However, complete revascularization using a single method may not always be possible. Results of the study enrolling 83,695 patients indicate that in the group of patients who underwent complete myocardial revascularization using the PCI and CABG methods, the mortality rate was lower in those who underwent complete myocardial revascularization. Objective of the study was to analyze the medium-term treatment outcomes in patients with coronary heart disease and multivessel coronary artery damage who underwent PCI and CABG. Materials and methods. The treatment outcomes in 26 patients undergoing myocardial revascularization by means of combining two methods – percutaneous coronary intervention (PCI) and off-pump CABG – were analyzed. The observation time was 25.0 ± 9.6 months. Results and discussion. The survey data obtained included the scores of the Seattle Questionnaire developed by Spertus J. et al. [6] and Holter monitoring data. The medium-term results of EchoCG have been analyzed. Medium-term observational results showed 100 % survival rate, 1 (3.8 %) case of myocardial ischemia recurrence, 1 (3.8 %) case of re-revascularization; neurological events were not revealed. Conclusions. The medium-term results obtained indicate the effectiveness and safety of this approach.